Tax Compliance During the Covid-19 Pandemic: A Literature Review - Wiandini Sranti Palupi; Negina Kencono Putri (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2021)
The Covid-19 pandemic has influenced various sectors in Indonesia. The government provides economic stimulus policies, one of which is tax incentives. Several studies have been carried out but show the fact that the relationship between tax incentives and tax compliance has not yet produced an agreement. So that the researchers conducted a literature review to be more in-depth to find out how studies on the effect of tax incentives on tax compliance have been carried out. The results show that the effect of tax incentives on compliance has not yet produced conclusive findings. In general, more formal compliance proxies are used by Indonesian researchers, researchers from other countries are more likely to employ material compliance proxies. The use of primary data through questionnaires is becoming more dominant by researchers in Indonesia, while researchers from abroad use secondary data more. The research approaches used to discover greater tax compliance because of tax incentives are diverse.